Effects of biofuel on engines performance and emission characteristics: a review - Altarazi, Yazan S. M.; Abu Talib, Abd Rahim; Yu, Jianglong; Gires, Ezanee; Abdul Ghafir, Mohd Fahmi; Lucas, John; Yusaf, Talal (Energy, 2022)
Alternative fuels are still needed to compensate for the energy shortages caused by fossil fuel depletion. The paper aims to brief the types of alternative fuels used for the past 30 years. Moreover, it includes the recent types of biofuels (especially biodiesel) and their blends with studies on the performances and the exhaust emissions for different engines. In this study, previous studies were analysed, the challenges faced by the researchers were examined, and incentives for using biodiesel fuel in engines were discussed. The engine performance and emissions when using biodiesels and their blends in different engine models were also surveyed. All biodiesels and their blends have demonstrated the ability to reduce emissions such as carbon oxide (CO), carbon dioxide (CO2), nitrogen oxide (NOx), particulate matter (PM) and hydrocarbon (HC) under various operating conditions, as well as the ability to improve the performance of the gas turbine. It is necessary to understand the combustion properties of fuels for their use in an engine. The contribution of this review is to help the engine manufacturers and researchers develop further research relating to readjusting and optimising the biodiesel engine and its relevant system.